Ovarian tissue cryopreservation and transplantation among alternatives for fertility preservation in the Nordic countries - compilation of 20 years of multicenter experience - Rodriguez-Wallberg, Kenny A.; Tanbo, Tom; Tinkanen, Helena; Thurin-Kjellberg, Ann; Nedstrand, Elizabeth; Kitlinski, Margareta Laczna; Macklon, Kirsten T.; Ernst, Erik; Fedder, Jens; Tiitinen, Aila; Morin-Papunen, Laure; Einarsson, Snorri; et al. (Acta Obstetricia et Gynecologica Scandinavica, 2016)
Introduction. The aim of this study is to report the current status of ovarian tissue cryopreservation among alternatives for fertility preservation in the Nordic countries. Material and methods. A questionnaire was sent to 14 Nordic academic reproductive centers with established fertility preservation programs. It covered fertility preservation cases performed up to December 2014, standard procedures for ovarian tissue cryopreservation and oocyte cryopreservation and reproductive outcomes following ovarian tissue transplantation. Results. Among the Nordic countries, Denmark and Norway practice ovarian tissue cryopreservation as a clinical treatment (822 and 164 cases, respectively) and their programs are centralized. In Sweden (457 cases), ovarian tissue cryopreservation is practiced at five of six centers and in Finland at all five centers (145 cases). Nearly all considered ovarian tissue cryopreservation to be experimental. In Iceland, embryo cryopreservation is the only option for fertility preservation. Most centers use slow-freezing methods for ovarian tissue cryopreservation. Most patients selected for ovarian tissue cryopreservation were newly diagnosed with cancer and the tissue was predominantly retrieved laparoscopically by unilateral oophorectomy. Only minor complications were reported. In total, 46 women have undergone ovarian tissue transplantation aiming at recovering fertility, 17 healthy children have been born and several additional pregnancies are currently ongoing. Whenever patients' clinical condition is permissive, oocyte cryopreservation after hormonal stimulation is preferred for fertility preservation. Between 2012 and 2014, a smaller proportion of females have undergone fertility preservation in the Nordic centers, in comparison to males (1: 3). Conclusions. Overall, ovarian tissue cryopreservation was reported to be safe. Slow freezing methods are still preferred. Promising results of recovery of fertility have been reported in Nordic countries that have initiated ovarian tissue ...